Vorarbeiten zu einer Königsliste Kaukasisch-Iberiens 7. Das Zeitalter des Wachtang Gorgasal - Schottky, Martin (Anabasis. Studia Classica et Orientalia, 2020)
Vaxtang I of Iberia, grandson of Arch´il, became king at the age of seven. In the beginning he was a loyal adherent of the Sasanian great-king, whom he supported in the Lazian war against Byzantium. But in 482, he abolished Vazgēn, the rebellious and apostate pitiaxš of Gogarene, and joined the Armenian insurrection against Persian religious oppression. However, the allied forces of Iberia and Armenia were beaten in a decisive battle on Iberian territory in 483. In the aftermath, only the Great King’s Peroz’s defeat and death in his last war against the Hephthalites (White Huns) in 484 saved Vaxtang from disaster. In later years his behaviour was rather unobtrusive and apparently faithful towards his Sasanian overlords. He died (maybe peacefully) at the age of about sixty between 499 and 502. Not before the 9th century Vaxtang was styled as a great warrior for Iberian Christianity. He then got the sobriquet Gorgasali, “Wolf’s Head”, which is sometimes wrongly interpreted as Gorgaslani, “Wolf-Lion”. At present, Vaxtang Gorgasali, the alleged founder of T’bilisi, is the uncontested Georgian national hero. Between 1289 and 1724 five Bagratid kings ruled in Georgia, who were named Vaxtang after him.